Policy mix: mess or merit?. Issue 1 (2nd January 2019) - Bouma, J. A.; Verbraak, M.; Dietz, F.; Brouwer, R.
ABSTRACT: Many researchers and policy makers have called for optimal policy mixes to address major issues such as climate change and biodiversity conservation. This paper i) screens and reviews the wider academic literature to define the concept of policy mixes; ii) discusses the justifications for using a policymix and iii) explores the methodologies for evaluating them. In defining a policymix we distinguish between policy objective mixes and policy instrument mixes. Justifications for policy objective mixes generally lie in the domain of distributional concerns and other political issues, whereas justifications for policy instrument mixes are mostly related to specific market, governance or behavioural failures. We reflect on the different justifications and discuss their role in policy mix design and evaluation. We consider the challenges of policy mix evaluation and discuss the potential of experimental methods for policy evaluation and design. We conclude that the design and evaluation of policy mixes requires a mix of methods, since no single method can effectively assess the various welfare impacts of different policy instruments. In addition, we recommend that a policymix evaluation starts by disentangling the different policy objectives, means and instruments in order to be able to define, justify and assess the societal impact and cost-effectiveness of policy instrument design.